ANALYSIS OF LIMONENE AND OTHER ANTIOXIDANTS IN COMMERCIALESSENTIAL OIL PRODUCTS COMPARED TO HOMEMADE VIRGIN COCONUT OIL - Suaniti, Ni Made; Adnyana, I Wayan Bandem; Manurung, Manuntun; Ratnayani, Oka; Anjani, Raisyah (International Journal of Biosciences and Biotechnology, 2020)
Essential oil production in the market is very diverse with various brands labeled as antioxidants that have gained more attention in the society recently. The purpose of this study was to analyze limonene and other antioxidants content of the essential oils in the market compared to homemade virgin coconut oil. The method used was Gas Chromatography-Mass Spectrometry (GC-MS) and Fourier-transform infrared (FTIR) Spectroscopy. The infrared spectrogram showed the presence of alkanes and esters respectively at wave numbers of 3000-2850 and 1750-1730 cm-1. Chromatogram results showed the presence of limonene compounds and some antioxidants with a fairly good separation in the several types of oils, which was not detected in the homemade virgin coconut oil.